2018
DOI: 10.1007/s11205-018-1937-9
|View full text |Cite
|
Sign up to set email alerts
|

It Deepens Like a Coastal Shelf: Educational Mobility and Social Capital in Germany

Abstract: The prospects for the next generation-whether young people, regardless of their backgrounds, have equal chances of social success-pose a momentous problem for modern societies. Inequality of opportunity, often reflected by social immobility, is a threat to the egalitarian promise and the stability of your society. This work argues that social capital transmission plays an important role for the chances of social success in Western societies. For the example of Germany, it is reasoned that weak social capital e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Among several other empirical results, it has been shown that trust can be associated with higher rates of economic growth [Knack and Keefer, 1997] and better financial [Guiso et al, 2000] and educational [Stephany, 2019] development. It has been shown that bureaucracies [Porta et al, 1996] and education systmes [Alesina et al, 1997] work better in a high trust environment.…”
Section: The Benefits Of Trustmentioning
confidence: 99%
“…Among several other empirical results, it has been shown that trust can be associated with higher rates of economic growth [Knack and Keefer, 1997] and better financial [Guiso et al, 2000] and educational [Stephany, 2019] development. It has been shown that bureaucracies [Porta et al, 1996] and education systmes [Alesina et al, 1997] work better in a high trust environment.…”
Section: The Benefits Of Trustmentioning
confidence: 99%
“…The larger the share of digital natives 4 , the less time and effort is required to convince citizens about the effectiveness and security of digital solutions [5,6]. Thirdly, successful digital (government) services demand trust [7][8][9][10]. In fact, this aspect is quite visible for the Estonia case.…”
Section: Literaturementioning
confidence: 99%
“…2 At the same time, a society's level of generalized trust is strongly related to societal settings, such as inequality (Stephany, 2017) or educational attainment (Stephany, 2019).…”
Section: Introductionmentioning
confidence: 99%